The Impact of Business Intelligence on Digital Marketing Activities: The Mediating Effect of Technological Capabilities - Alzyadat, Mohammad Awad (International Review of Management and Marketing, 2025)
This research examines how Business Intelligence (BI) and Technological Capabilities (TC) cumulatively impact Digital Marketing (DM) performance in industrial companies, based on empirical data from Jordan. Drawing on Resource-Based View and Dynamic Capabilities Theory, the research formulates and examines a conceptual framework where BI constitutes a strategic resource and TC represents a key marketing effectiveness enabler. Data were obtained from 252 managerial respondents from different manufacturing industries by using a structured questionnaire. Covariance-Based Structural Equation Modeling (CB-SEM) was used to test associations. The findings indicate that BI has direct and indirect impacts on DM performance, where TC represents an essential mediating variable. These results underscore that although BI facilitates data-based marketing decisions, its strategic advantage depends on internal technological readiness of the firm. The research contributes to knowledge by validating an integrated BI–TC–DM framework in an emerging market industrial setting and enhances practical knowledge by illustrating how digital infrastructure can be aligned with analytics to enhance marketing outcomes. The findings have particular relevance to industrial companies facing digital transformation as well as policymakers seeking to support Industry 4.0 implementation within resource-scarce environments.